BIOACTIVE COMPONENTS OF GYNURA DIVARICATA AND ITS POTENTIAL USE IN HEALTH, FOOD AND MEDICINE:A MINI-REVIEW - Xu, Bing-Qing; Zhang, Yu-Qing (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: G. divaricata (L.) DC belongs to genus the Gynura Cass which is a kind of perennial herb that has goodhealth protection efficacy and is especially used widely in medicine and functional food. It is one of the most famoustraditional Chinese medicinal herbs and is usually used to cure bronchitis, pulmonary tuberculosis, kink cough,rheumatism, diabetes, and so on. It has a long history for the treatment of diabetes mellitus in the folk medicine. Thisreview is aimed at gathering all information relating to G. divaricata and obtaining new insights for further studies on G.divaricataMaterials and Methods: PubMed, Springer Link, Web of Science, Science Direct and Research Gate were used for theliterature search. The key search terms included G. divaricata isolation and identification, flavonoids and theircombinations without language restriction. The period for the search is from year 1979 to 2016.Results: The main chemical components were listed, and the folk application, the extraction and separation methods ofmain chemical components, pharmacological effects of G. divaricata were discussed, which further demonstrated theplant’s value as health food and medicine.Conclusion: The present review is of great significance to the development of new medicinal resources and health foodof G. divaricata